Pesan Dakwah pada Upacara Adat Ngeuyeuk Seureuh - Zazam Khairul Umam; Karsidi Diningrat; Asep Iwan Setiawan (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2017)
This study is to know the form of traditional ceremony Ngeuyeuk Seureuh, and the messages of da'wah contained in the ceremony in the village of Palintang Village Cipanjalu Village District Cilengkrang Bandung. The formulation of the problem in this research is how the form or way of traditional ceremony Ngeuyeuk Seureuh and the message of dakwah at traditional ceremony Ngeuyeuk Seureuh. The method used is descriptive method, which presents a complete picture of social life and phenomenon of traditional ceremony Ngeuyeuk Seureuh in Kampung Palintang. Based on the results of research, has obtained the result that the traditional ceremony Ngeuyeuk Seureuh is a series of traditions at the wedding ceremony in tatar Sunda which has been implemented for generations. This tradition is usually held one day before the wedding day at home of the bride in the morning or evening. In the traditional ceremony Ngeuyeuk Seureuh there are messages of Islamic propaganda. The message of Da'wah in Ngeuyeuk Seureuh traditional ceremony is divided into two namely verbal and non verbal message of da'wah. The message of verbal da'wah contained in traditional ceremony Ngeuyeuk Seureuh is taken based on al-qur'an and hadith, while non verbal message of dakwah is found in all parts of traditional ceremony media Ngeuyeuk Seureuh. Penelitian ini untuk mengetahui bentuk upacara adat Ngeuyeuk Seureuh, dan pesan-pesan dakwah yang terdapat dalam upacara adat tersebut di Kampung Palintang Desa Cipanjalu Kecamatan Cilengkrang Kabupaten Bandung. Adapun rumusan masalah dalam penelitian ini adalah Bagaimana bentuk atau cara upacara adat Ngeuyeuk Seureuh dan pesan dakwah pada upacara adat Ngeuyeuk Seureuh. Metode yang digunakan adalah metode deskriptif, yaitu menyajikan gambaran lengkap mengenai kehidupan sosial dan fenomena terhadap upacara adat Ngeuyeuk Seureuh di Kampung Palintang. Berdasarkan hasil penelitian upacara adat Ngeuyeuk Seureuh merupakan suatu rangkaian tradisi pada upacara pernikahan di tatar Sunda yang telah dilaksanakan secara turun-temurun. Tradisi ini biasanya dilaksanakan satu hari sebelum hari pernikahan di rumah calon mempelai wanita pada pagi hari atau malam hari. Dalam upacara adat Ngeuyeuk Seureuh ini terdapat pesan-pesan dakwah Islam yang terbagi menjadi dua yaitu pesan dakwah verbal dan non verbal. Pesan dakwah verbal yang terkandung dalam upacara adat Ngeuyeuk Seureuh diambil berdasarkan Alquran dan hadis, sedangkan pesan dakwah non verbal terdapat pada semua bagian media upacara adat Ngeuyeuk Seureuh.